Aggregate-level analysis and prediction of midterm senatorial elections in the United States, 1974-1986. - Lichtman, A J (1989)
Pattern recognition study demonstrates that the outcomes of American midterm senatorial elections follow the dynamics of simple integral parameters that depict preelectoral situations aggregated to the state as a whole. A set of "commonsense" parameters is identified that is sufficient to predict such elections state-by-state and year-by-year. The analysis rejects many similar commonsense parameters. The existence and nature of integral collective behavior in U.S. elections at the level of the individual states is investigated. Implications for understanding the American electoral process are discussed.